Risk Factor of HIV Infection Among Young Agein Voluntary Counseling Testing (VCT) Clinics of Yogyakarta - Ismael Saleh; Sumardi Sumardi; Lutfan Lazuardi (Pusat Kedokteran Tropis, 2013)
ABSTRACTIntroduction: HIV/AIDS is a health problem in the world. The Highest HIV/AIDS cases in Indonesia were reported in young age groups, including in Province of Yogyakarta (DIY). Knowing the determinant and risk factors of HIVis necessary to determine effective prevention programs, especially in young agewhich one of the vulnerable populations, either because of individual and family characteristics, media influence, peer pressure, substance use and risky behavior.Objectives: To know the relationship between risk factors for HIV infection amongyoung age in VCT clinic of Yogyakarta.Methods: This study used a cross-sectional design and the population was young clients at VCT clinics of Yogyakarta. Samples were obtained from VCT clinics of Griya LenteraPKBI Yogyakarta and Edelweis Clinics of Dr Sardjito Hospital. Variable risk factors were obtained byquestionnaire and interviews than HIV test results was obtained from VCT clinics.Results: Of the 62 respondents, 74.2% were female, age average were 24,4 years old, 41.9% level education were junior high school, 82.3% had migration, 62.9% received less monitoring from families, 61.3% ever use the TV / HP for pornography, 56.5% getting high sexual pressure from peers, 62.9% had been smoking and alcohol consumption, 98.4% had ever sexual intercourse, 95.2% had sexual intercourse in the last 6 months, 93.5% risky sexual intercourse, 32.3% HIV positive and 55% through heterosexual.Conclusion: HIV infection among young people in VCT Clinic of Yogyakarta, by bivariate analysis correlated with gender, residency status, education level, relationship with parents, TV / mobile and internet used to watch pornography. However, according to multivariate analysis, HIV infection correlated with education level at senior high school and college, residing with their parents/ family and in the last 6 months are still using alcohol and illicit drugs. It is recommended to enhance more comprehensive prevention for young people in accordance with the factors associated with HIV risk behaviour.Keywords: HIV infection, young age, individual characteristics, family, peers, media usage, substance use, risky behavior.